FIVE EFFORTS OF ISLAMIC EDUCATION TEACHERS IN GUIDING STUDENTS SLOW LEARNER IN ELEMENTARY SCHOOL - Anisah Permatasari; Indah Muliati; Jurnie Darakay (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2023)
Individual differences that exist in students in the class must be a concern for the teacher. In that difference there are students who are fast, moderate and slow. In carrying out teaching tasks, teachers should not only focus on students who are smart and vice versa, teachers should not only focus on students who are slow. So this study aims to examine the efforts of Islamic Religious Education teachers in guiding slow learner students. This study uses a qualitative method with a case study approach. Research data was taken from three informants through in-depth interviews consisting of curriculum representatives, Islamic Religious Education teachers, and Special Advisor teachers. All interview and observation data were analyzed using the Milles & Hubberman Analysis Interactive model. The results of this study found five efforts made by Islamic Religious Education teachers to guide slow learner students, namely: i) Individual approach, ii) Learning media, iii) Giving praise, iv) Providing motivation, and v) Coordinating with parents. This research can provide knowledge of the steps taken by teachers to deal with slow learners so that they can improve learning management.